Identification of short-wavelength contact wire irregularities in electrified railway pantograph–catenary system. (August 2021) - Song, Yang; Rønnquist, Anders; Jiang, Tengjiao; Nåvik, Petter
Highlights: Propose two approaches to identify catenary short-wavelength irregularity. 1/8 of dropper interval wavelength can reflect effect of local imperfection. Periodic irregularity introduces non-Gaussian behaviour into contact force. Time-frequency representation can be used to detect periodic irregularity. Abstract: The effect of two common types of short-wavelength irregularities (local imperfections and periodic short-wavelength irregularities) of the railway catenary on the pantograph–catenary interaction performance are studied and their potential identification approaches are explored in this paper. The analysis of the intrinsic mode functions of panhead acceleration indicates that the effect of local imperfection can be reflected in the high-order deformation mode of the contact wire. The cut-off frequency is suggested to cover the wavelength smaller than 1/8 of the dropper to dropper distance, which can be used to identify the local imperfection. The instantaneous energy obtained by the Hilbert transform is used to localise the local imperfection. The effect of periodic short-wavelength irregularities can be recognised as the introduction of non-Gaussian behaviour in the contact force at specific wavelengths. Thus, spectral kurtosis is utilised to identify the deviating wavelength. The short-wavelength irregularity can be localised by the time-frequency analysis of the intrinsic mode function containing the identified deviating wavelength. The examples with measurement data indicate the validation of the present methods with some improvements to the current equipment.